Technological innovations and the interest rate - Leão, E. R. (2007)
We build a dynamic general equilibrium model where there are banks that charge interest for their loans to the private sector. We look at the response of the interest rate to innovations in the banks’ technology and to innovations in the nonbank firms’ technology. We find that whereas technological innovations in the nonbanking sector put upward pressure on the interest rate, technological innovations in banks exert downward pressure on the interest rate. This property of the model is behind our main result: in stochastic simulation experiments where the technological shocks in banks are highly positively correlated with the technological shocks in firms, we obtain a strong negative correlation between the current interest rate and future values of real output. This corresponds to what the data show us [see King and Watson (1996)].